Visitor characteristics and perceptions of Cadika Park Medan during the COVID-19 pandemic - Moehar Maraghiy Harahap; Alfan Gunawan Ahmad; Farah Amnestesia; Mariah Ulfa (Talenta Publisher, 2025)
Cadika Park is a public green space in Medan, North Sumatra, Indonesia. TheCOVID-19 virus originated in Wuhan, China, in 2019 and spread throughoutIndonesia in early 2020. During the pandemic, Cadika Park became a venue wherepeople could engage in their daily activities while enjoying various naturalbenefits that aid in restoring both physical and psychological health. This studyaims to analyze the characteristics and perceptions of visitors regarding themanagement, services, and facilities of Cadika Park during the COVID-19pandemic. The number of respondents was determined using the Slovin formula,and a purposive sampling technique was employed to select participants. Dataanalysis used a descriptive quantitative frequency table to assess visitors'perceptions based on closed questions using the Likert Scale. The results indicatedthat adult women were the predominant characteristic of visitors to Cadika Parkduring the pandemic. Most visitors had jobs or were students from outside theMedan Johor sub-district. They typically had an education level between 9 and 18years and used motorcycles as their primary mode of transportation. Overall,visitors positively perceived the aspects studied, with many returning to the parkfrequently during the COVID-19 pandemic